India-UAE Security Ties: Moving Towards an Enduring Partnership. Issue 2 (3rd March 2020) - Pradhan, Prasanta Kumar
Abstract: Traditionally dominated by the trade, energy and Diaspora ties, the India-UAE relationship has been growing substantially in the security arena in recent years. There are deliberate and robust attempts from both sides to forge strong security cooperation. The high volume of trade and commerce, common threat perceptions such as terrorism and piracy, continuing regional instability in West Asia since 2011 are some of the key drivers of the growing India-UAE security cooperation. Recent high-level visits have provided the much needed confidence to both sides to engage in the security domain. The relationship has strong potential to grow in the future, given the persisting fragile security environment in their neighbourhood.